(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article explores the intersection of contrastive linguistics and intercultural communication, emphasizing the pivotal role contrastive linguistics plays in facilitating effective communication across cultural boundaries. It delves into the fundamental concepts of contrastive linguistics, elucidating its purpose in comparing and contrasting languages to identify structural, grammatical, and functional differences. The article emphasizes the significance of this discipline in understanding intercultural communication, highlighting its ability to anticipate and address communication barriers arising from linguistic disparities. It elucidates how contrastive linguistics serves as a bridge between languages, aiding in cultural sensitivity, language learning strategies, and navigating professional contexts. The article acknowledges the challenges in this field while proposing potential future directions, such as leveraging technology and computational linguistics for more comprehensive analyses. Overall, it underscores the indispensable role of contrastive linguistics in promoting mutual understanding and cooperation across diverse cultures and languages in our increasingly interconnected global landscape.